Dexmedetomidine prescribing in Australian intensive care units: an observational study. (30th May 2019) - O'Brien, Daniel W.; Cotta, Menino O.; Choo, Lyn; Fowler, Stephen; Downey, Maria; Fisquet, Stephanie; Tan, Ivy; Roberts, Jason A.
Abstract: Dexmedetomidine is used in the intensive care unit (ICU) as a short‐term sedative. The data included in the manufacturer's product information is controversial, and there is little consensus to guide initial dosing and titration. This observational study surveyed the practice of dexmedetomidine use in Australian ICUs. An expression of interest (EOI) for a multisite observational study was sent to members of the ICU email group of the Society of Hospital Pharmacists Australia (SHPA). Participating members collected treatment‐related data for patients meeting inclusion criteria between January 2013 and July 2014. Six of 14 sites that responded positively to the EOI returned complete datasets, and 232 patients met the inclusion criteria. The main reported indications for dexmedetomidine use across the six sites were to manage agitation (33.2%), to aid extubation (32.8%) and to sedate (34.0%). The median duration of therapy was 42 h (range 1–672 h). Only nine patients (3.9%) received loading doses. The median maximum dose used for maintenance therapy in patients ranged from 1.2 to 4.0 microgram/kg per h. There was a significant disparity of practice across sites, as evidenced by differences in reported indication, off‐label use, rates of loading doses and doses used for maintenance therapy. Consensus prescribing guidelines are required to guide more consistent and evidence‐based prescribing of dexmedetomidine.